Use Of Sofi Alloyor's Moral And Educational Knowledge In Improving Social And Cultural Skills Of Students - Aliyeva Bashorat Ergashovna (Euro Asian Journal Publishing, 2025)
This article analyzes the issue of using the moral and educational knowledge of Sofi Alloyor in the formation of socio-cultural skills of students. Sofi Alloyor's moral ideas and approaches in the field of education play an important role in the spiritual development of young people. This article shows how her moral and educational views can be used in the development of social and cultural skills of students
Keywords: Sufi Alloyor; ethics; enlightenment